2018
DOI: 10.2217/mmt-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Adverse Events with Combination of Checkpoint Inhibitors in Advanced Melanoma: A Systematic Review

Abstract: Introduction:Immunotherapies, including checkpoint inhibitors (CIs) such as cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed death-1 (PD-1) inhibitors, are revolutionizing the treatment of advanced melanoma. Combining CTLA-4 and PD-1 inhibitors provides additional clinical benefit compared with single agents alone. However, combination therapy can increase the incidence of gastrointestinal adverse events (GI AEs). This systematic review assessed the epidemiological, clinical, economic, and humanistic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…GI adverse events were graded using the US National Cancer Institute (NCI) Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. These criteria generally grade irAEs on a scale of 1 - 5 (1 = mild event/reaction, 2 = moderate event/reaction, 3 = severe event/reaction, 4 = life-­threatening event/reaction, 5 = death) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…GI adverse events were graded using the US National Cancer Institute (NCI) Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. These criteria generally grade irAEs on a scale of 1 - 5 (1 = mild event/reaction, 2 = moderate event/reaction, 3 = severe event/reaction, 4 = life-­threatening event/reaction, 5 = death) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ntali and colleagues (2017) have made a careful review of the literature regarding the endocrine sequelae of cancer immunotherapy, showing that these treatments may lead to hypophysitis, adrenalitis and both hypothyroidism and hyperthyroidism depending on specific characteristics of patients [196]. Finally, as observed for several chemotherapeutic agents, also the administration of immune checkpoint inhibitors is correlated to several gastrointestinal side effects mainly including diarrhea, colitis, nausea, vomiting and abdominal pains [197]. Furthermore, adverse effects including rash or pruritus, thyroiditis, hypothyroidism or hypophysitis and asymptomatic pancreatitis were reported in dMMR cancer patients treated with PD-1 blockade [198].…”
Section: Immunotherapeutic Approaches Against Cancermentioning
confidence: 99%
“…[66] For example, a systematic review that assessed the clinical, epidemiological, humanistic, and economic burden of gastrointestinal AEs due to combination checkpoint inhibitors in advance melanoma reported that patients who received combination of ipilimumab plus nivolumab experienced more AEs than patients who received monotherapy checkpoint inhibitors. [68] Similarly, an observational study of patients with nonsmall cell lung cancer receiving nivolumab plus an EGFR-tyrosine kinase inhibitor (TKI) reported higher incidents of interstitial pneumonitis for nivolumab in combination with EGFR-TKI versus treatment with either drug alone. [69]…”
Section: Categories Of Immunotherapymentioning
confidence: 99%